Resiliencia y calidad de vida en niños/as y adolescentes de la Casa Hogar “San Carlos”.Riobamba.marzo-julio 2017 - Molina Moncayo, Liliana Corali (2018)
The present rescarch projcct has the objectivc to analyze the lcvel of rcsilience and quality of chíldren and adolescents' life of the Casa Hogar 11Sa11 Carlos". Riobamba, Marzo-Julio 2017, thcoretically \VC can mcntion that thc rcsilicnce is thc ability to overcome the adverse cvents, and be nble to havo a successful dcvclopmcnt in spite of circumstances, so this population is vulnerable to a variety of cireumstances ; thc lifc 's c¡ualily in thc pcrccption of thc individual on its position in the lifc iuside tite cultural contcxt and thc systcm of vnlues in ,vhich thcy livc and with rcspcct to thcir goals, expcctations, uorms and couccrns, Thc mcthodology uscd was thc deductivo mcthod-inducuve, analytic-synthctic; with a rcscarch dcsign non-experimental, the typc of invcstigalion was bibliographic ficld, transvcrse; according to the lcvcl of rcscarch wns descriptivo and correlatioual stucly , thc population werc childrcn and adolcsccnls with a samplc of 15 childrcn and adolesccnts of tite Casa l logar "San Carlos". Thc sample was random and inteutional, thc techniqucs that were used psychomctrics as instruments was applicd thc Sea le of rcsilicncc of Wagnild and Young and Scale Gencat, thc sanie that contributcd to thc analysis of thc rcsult to reach thc couclusicn thnt chiicircn aud adotcsccnts are al a mcdium levcl in the resilicncc, due to thc conditions oflifc's quality that thcy havc in the "Casa Hogar"